Infrequent Histopathologic Subtypes of Oral Squamous Cell Carcinoma: A Case Series with Emphasis on Histopathologic Characteristics - Saede Atarbashi Moghadam; Ali Lotfi; Leyla Roghanizadeh; Seyed Sepehr Mirebeigi Jamasbi; Zeinab Akbarzadeh Fathabadi (Journal of Dentistry)
Squamous cell carcinoma (SCC) is the most common oral malignancy. Conventional types are classified as well-, moderately- and poorly differentiated, which are usually easy to diagnose microscopically. Still, uncommon variants such as basaloid, verrucous, spindle cell, papillary, adenosquamous, acantholytic, cuniculatum, clear cell, and pigmented SCC make a diagnostic challenge for pathologists. This report presents four rare cases of oral SCC with histopathologic diagnosis of spindle cell carcinoma, carcinoma cuniculatum, papillary SCC, and basaloid SCC focusing on microscopic characteristics and differential diagnosis. The apprehensive knowledge about the unique histopathologic features of these uncommon variants is crucial to avoid their misdiagnoses and provide appropriate treatment.